The Beguniaceae of Colombia The Beguniaceae of Colombia - Smith Lyman B.; Schubert Bernice G. G. (Caldasia)
Begonia (§ Ruizopavonia) Dugandiana / Begonia (§ Ruizopavonia) alnifolia / Begonia (§ Pritzelia) glabra / Begonia (§ Begoniastrum) guaduensis / Begonia (§ Begoniastrum) Barrigae / Begonia (§ Meionanthera) Holtonis / Begonia (§ Lepsia) microphylla / Begonia (§ Lepsia) foliosa  / Begoniella / Begoniella Whitei / Begoniella libera / Begoniella Kalbreyeri / Begoniella angustifolia. <span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: ES; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Begonia (§ Ruizopavonia) Dugandiana / Begonia (§ Ruizopavonia) alnifolia / Begonia (§ Pritzelia) glabra / Begonia (§ Begoniastrum) guaduensis / Begonia (§ Begoniastrum) Barrigae / Begonia (§ Meionanthera) Holtonis / Begonia (§ Lepsia) microphylla / Begonia (§ Lepsia) foliosa  / Begoniella / Begoniella Whitei / Begoniella libera / Begoniella Kalbreyeri / Begoniella angustifolia.